2021
DOI: 10.3390/plants10112240
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Accumulation in Fruit Peel and Expression Profiling of Related Genes in Purple (Passiflora edulis f. edulis) and Yellow (Passiflora edulis f. flavicarpa) Passion Fruits

Abstract: Flavonoids play a key role as a secondary antioxidant defense system against different biotic and abiotic stresses, and also act as coloring compounds in various fruiting plants. In this study, fruit samples of purple (Passiflora edulis f. edulis) and yellow (Passiflora edulis f. flavicarpa) passion fruit were collected at five developmental stages (i.e., fruitlet, green, veraison, maturation, and ripening stage) from an orchard located at Nanping, Fujian, China. The contents of flavonoid, anthocyanin, proanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 68 publications
2
14
0
2
Order By: Relevance
“…Citrus juices are well known as complex mixtures of organic acids and sugars [1,2]. Sugar and organic acid are major soluble components in ripe fruits and have vital roles in fruit taste and flavor, which are key indicators of fruit quality [3][4][5][6][7][8][9]. Their nature and concentrations significantly contribute to the perception of citrus juices [10].…”
Section: Introductionmentioning
confidence: 99%
“…Citrus juices are well known as complex mixtures of organic acids and sugars [1,2]. Sugar and organic acid are major soluble components in ripe fruits and have vital roles in fruit taste and flavor, which are key indicators of fruit quality [3][4][5][6][7][8][9]. Their nature and concentrations significantly contribute to the perception of citrus juices [10].…”
Section: Introductionmentioning
confidence: 99%
“…The other phenolic acid compounds included tannins (valoneic acid, and vallinic acid glucoside), phenolic acid glucosides (protocatechuic acid glucoside, and galloyl shikimic acid di-HHDP-glucose), hydroxy gallic acid (derivative of gallic acid), and a coumaric acid derivative. Flavonoids have been detected in almost every part of the passion plant, including the leaves, pulp, and peel [ 55 ], and these compounds have been reported to possess health-promoting properties [ 56 ]. In the current study, the identified flavonoids (ca 22% of total) were classified as flavanols (epi)catechin-(epi)catechin, quercetin), flavones (acacetin rhamnoside) and flavonoid glycosides (4′-Methoxyluteolin-8-C-β-D-glucopyranoside, kaempferol-3,7,4′-O-triglucoside,luteolin-3-O-(6″-O-malonyl)-glucoside).…”
Section: Resultsmentioning
confidence: 99%
“…PgCHS, PgF3H, and PgDFR isolated in pomegranate are highly expressed in red fruits, and their transcript levels show a synchronous increase with the accumulation of flavonoids [43]. C4H, 4CL, and UFGT play a decisive role in anthocyanin production in passionfruit [44].…”
Section: Discussionmentioning
confidence: 99%